Transferable atoms: an intra-atomic perspective through the study of homogeneous oligopeptides. (17th April 2016) - Maxwell, Peter; Popelier, Paul L.A.
ABSTRACT: Quantifying an atom's transferability, in a force field context, demands a quantitative understanding of how an atom 'experiences' the surrounding environment both intra-atomically and inter-atomically. Here we investigate the intra-atomic ( E intra A ) viewpoint through the study of the atoms Cα, Hα, N, O, and S in a series of 'mono'-, tri- and penta-peptides. The remaining inter-atomic viewpoint consists of an electrostatic (via multipole moments), exchange and correlation components respectively, of which the electrostatic component has been previously reported. Together these four energy components, as calculated from the Interacting Quantum Atoms (IQA) partitioning approach, express the foundation of the Quantum Chemical Topological Force Field (QCTFF). In order to have transferability within a force field, smaller sample systems must be calculated and developed as representative of larger target systems. The Cα, Hα, N, O and S atoms in a tri-peptide are energetically comparable to those in their penta-peptide configurations, within 2.1 kJ/mol in absolute value (1 exception). Across all five elements, this energy difference is on average ∼0.3 kJ/mol. On average, the tri-peptide sample systems represent a ∼8.2 Å atomic horizon around the central atoms of interest. Thus, both the previous knowledge of the ∼10.3 Å horizon sphere and ∼0.4 kJ/mol error required by the electrostatic multipole moments, determine how two of the four key QCTFF energy components are affected by an atom's molecular environment. GRAPHICAL ABSTRACT: